Perception de la coordination des soins et appréciation de la vie chez les jeunes adultes atteints de cancer: étude corrélationnelle en contexte oncologique marocain - Lamya Lamrani (Darul Yasin Al Sys, 2026)
Cancer care extends beyond biomedical management and includes organizational factors that may influence patients’ subjective well-being. This study aimed to examine the association between perceived care coordination and life appreciation among young adult cancer patients. A quantitative study was conducted with 209 oncology patients. Perceived care coordination was assessed using the PCCCT-14 questionnaire, previously adapted and validated in Arabic. Pearson’s correlation analysis was performed. A positive and statistically significant correlation was found between perceived care coordination and life appreciation (r = 0.335; p < 0.005). Better perceived care coordination is associated with higher life appreciation, highlighting the importance of organizational aspects of care in shaping patients’ subjective experiences in oncology.